Identification of the AKCDPK gene family and AkCDPK15 functional analysis under drought and salt stress - Penghua Gao; Ying Zou; Min Yang; Lifang Li; Ying Qi; Jianwei Guo; Yongteng Zhao; Jiani Liu; Jianrong Zhao; Feiyan Huang; Lei Yu (PLoS ONE, 2025)
Konjac is one of the important economic crops for poverty alleviation in mountainous areas of Yunnan Province, China. However, there are always various biotic and abiotic stress during its growth, leading to production reduction and quality decline. Calcium-dependent protein kinases (CDPKs) are an important class of genes involved in calcium ion signal transmission within plant tissue cells, yet their presence and functions in konjac remain unexplored. This study aimed to identify the members of the AkCDPK gene family in the Amorphophallus konjac genome and understand their evolution and responses to various stresses. A total of 29 AkCDPK genes were identified and categorized into four subgroups that unevenly distributed across 12 chromosomes. Most AkCDPK have undergone purifying selection during evolution. Cis-acting element analysis revealed that several AkCDPK are involved in phytohormone induction, defence, stress response, and plant development. Expression analysis indicated tissue specificity, and responses to salt, drought, and Pectobacterium carotovorum subsp. carotovorum stress. AkCDPK15, encoding 582 amino acids, was cloned. AkCDPK15 was mainly localised on the cell membrane, and overexpression in tobacco revealed that it can positively regulate the tolerance of transgenic tobacco strains to salt and drought stress. These findings provide a theoretical foundation for future research on the function of the CDPK gene family in A. konjac, potentially aiding in the development of stress-resistant konjac varieties.